New product development - X-Tube breast pump / Mohamad Izwan Roselan, Mohd Yusof Mohamed Fahmy and Mohammad Akhil Abdul Aziz - Roselan, Mohamad Izwan; XMohamed Fahmy, Mohamad Izwan; Abdul Aziz, Mohammad Akhil (2018)
Breastfeeding give a lot of benefits to the babies. In the national policy of breastfeeding, the Malaysian government had encouraged the mother to breastfeed their baby until the age of two years old. However, majority of mother nowadays is a working mother. Breastfeeding become a new challenge for them. The breast pump was designed to help these working mothers to manually pumping out the milk for their babies but the design was still bulky, messy with accessory and not mobile.